Interseismic Ground Deformation and Fault Slip Rates in the Greater San Francisco Bay Area From Two Decades of Space Geodetic Data. Issue 9 (7th September 2018) - Xu, Wenbin; Wu, Songbo; Materna, Kathryn; Nadeau, Robert; Floyd, Michael; Funning, Gareth; Chaussard, Estelle; Johnson, Christopher W.; Murray, Jessica R.; Ding, Xiaoli; Bürgmann, Roland
Abstract: The detailed spatial variations of strain accumulation and creep on major faults in the northern San Francisco Bay Area (North Bay), which are important for seismic potential and evaluation of natural hazards, remain poorly understood. Here we combine interferometric synthetic aperture radar data from the ERS‐1/2 and Envisat satellites between 1992 and 2010 with continuous and campaign GPS data to obtain a high spatial and temporal coverage of ground deformation of the North Bay. The SAR data from both ascending and descending orbits are combined to separate horizontal and vertical components of the deformation. We jointly invert the horizontal component of the mean velocities derived from these data to infer the deep strike‐slip rates on major locked faults. We use the estimated deep rates to simulate the long‐wavelength deformation due to interseismic elastic strain accumulation along these locked faults. After removing the long‐wavelength signal from the InSAR horizontal mean velocity field, we estimate fault‐parallel surface creep rates of up to 2 mm/year along the central section of the Rodgers Creek fault and surface creep rates ranging between 2 and 4 mm/year along the Concord fault. No surface creep is geodetically resolved along the West Napa and Green Valley fault zones. We identified characteristically repeating earthquakes on the Rodgers Creek fault, the West Napa fault, the Green Valley fault, and the Concord fault. Nontectonic deformation in the Geysers geothermal field and in Late Cenozoic basins (Rohnert Park and Sonoma basins) are also observed, likely due to hydrological and sediment‐compaction processes, respectively. Key Points: Interseismic ground deformation map of the greater San Francisco Bay Area is generated Deep strike‐slip rates on major locked faults are estimated Surface creeping signals are observed on the Rodgers Creek fault and the Concord fault